Making the links between women’s health and women’s lives in Papua New Guinea: Implications for policy and health care delivery - Hinton, Rachael (Curtin University, 2009)
International perspectives of women’s health have drawn on biomedical solutions and pathology-based aspects, and one of the main components of a changing and evolving definition of women’s health is to provide an alternative to these perspectives that are grounded in the western framework. There has been a tendency by researchers and health professionals to utilise approaches that prioritize only one dimension of woman’s lives such as their biological, reproductive or maternal roles to the detriment of understanding the complexity of women’s histories, cultural contexts and lived experiences. The overall goal of this study was to investigate women’s health within the socio-historical context of Papua New Guinea (PNG) to firstly, understand the self-identified heath concerns of women, secondly to examine the critical points in the lifespan for effecting positive change in the health status of women and finally, to ascertain if the divergence between the perceptions of service providers and the real needs of women can be reduced.The study was set in Patigo (Wosera sub-district), in the East Sepik Province, a rural area and one of the least developed areas of Papua New Guinea. There is a heavy reliance on subsistence production for household consumption, high infant and maternal mortality and morbidity rates, limited cash earning opportunities and low per capita incomes in the district. Women conduct most of the daily subsistence and domestic duties. Women’s health and social development statistics are poor in the Wosera and it is easy to see solutions as either medical or matters of health education. However the health status of women reflects the complex and changing social and structural conditions of women’s lives and in particular, the gender-based inequalities that women face are fundamental variables affecting health.This study was conceptualised using an interpretive qualitative methodology within an ethnographic and rights-based framework, based on the real experiences of women’s daily lives. The study was conducted during a four month study period from July to October 2005 and in February 2006. The investigation strategy utilised a within-method triangulation approach, using a combination of qualitative and participatory methods. To enable an understanding of the diverse health needs of women and the key determinants of health across the lifespan, the socio-cultural and gender perspectives of young, adult, older women were examined. Discussions were also held with young and adult men and key community members considered to have specific knowledge of women’s health issues.Women’s narratives show that reproductive health problems did not figure prominently among the health issues women described. Health was related to the social and material circumstances of women’s lives. It was discussed as a social and cultural experience, not an isolated and individual condition and all women prioritized people and relationships. Women were part of a nexus of complex social relationships that were socially and historically layered with links to many generations. The types of relationships women experienced were influenced by personality, faith and socio-cultural values.The relationship between women’s health and the social conditions of their lives is given token recognition in health policy and women’s health programming in Papua New Guinea. Women face a health system that pre-imposes a narrow definition of women’s health to the detriment of gender issues and women’s empowerment. The findings reveal that in the Wosera women’s work and the physical burden of women’s roles, marriage and risk and experience of violence, and an unresponsive and inappropriate health service were major risk factors and barriers to women’s health. Based on this finding a holistic and rights based approach to women’s health policy, programming and advocacy is proposed. It is argued that the daily inequalities, discrimination and oppression that women face in their everyday lives, affects their ability to achieve the right to health and a host of interrelated rights such as the right to education, right to food and nutrition and freedom from discrimination.The study also emphasized the relevance of psychosocial constraints for women’s health. Psychosocial factors, linked to material circumstances and individual behaviour, exerted a powerful influence over health and affected a woman’s ability to cope with difficult life circumstances. Feelings of powerlessness, helplessness and stress-related disorders among women were related to the gender inequalities that worked to perpetuate the low status of women throughout the life span. Women who could not count on male support (husbands, male relatives, sons) and were the target of constant abuse and neglect were identified to be particularly vulnerable and at a risk of depression and stress.The study also documented that women throughout the life cycle displayed inherent resilience and adopted different coping strategies for dealing with the demanding and complex circumstances of their lives but some women were better positioned than others to cope. The active coping mechanisms of women showed a strength, assertiveness and resourcefulness in response to constant hardship. Resilience was enhanced when women had access to social networks and supportive social relationships and were therefore better able to deal with constraints to health. A particular threat to coping was found to result from a woman’s experience with gender constraints, violence and lack of social support.The findings from this study contribute to a rethinking of the traditional biomedical approach to women’s health research. The study challenges the worldview that prioritizes reproductive health over an approach to women’s health that concerns the totality of women’s lived experiences throughout the life span. This study calls for the need to increase the focus of research on the application of psychosocial and rights-based perspectives to understand the diversity of women’s health-related experiences, the complexity of their social relations and the relationship between challenging social and material circumstances and health outcomes. Recommendation and implications for further research, education, policy, advocacy and programming action, are proposed and discussed.